Investigating the Negative Effects of Foreign Serials on the Spread of Social Violence and the Role of Islam in Its Prevention - Fazel, Muhammad Yasin (Journal of Social Sciences - Kabul University, 2021)
This study examines the negative effects of foreign television serials on Afghan society. Using a descriptive-analytical approach, the research explores how these serials contribute to social violence and anomalies, particularly among young people. The study delves into the root causes of violence and social instability and analyzes the role of media in shaping public behavior. The theoretical section discusses key concepts, including media influence, violence, and its various dimensions. The findings reveal that foreign serials contribute to increased aggression, the normalization of criminal behavior, the promotion of values contrary to Afghan cultural norms, the spread of mistrust among family members, and the rise of domestic violence. These factors play a significant role in the spread of social violence, particularly among the youth. The study also highlights the role of Islamic teachings in preventing these negative impacts and fostering a more harmonious society.